The age of ideology the 19th century philosophers - Aiken, Henry D. (Henry David) 1912-1982 (New York New American Library, 1956)
Basic writings of: Kant; Fichte; Schopenhauer; comte; Mill; Spencer; Marx; Mach; Nietzsche; Kierkegaard; Hegel.
Philosophy and ideology in the nineteenth century -- The transcendental turn in modern philosophy : Immanuel Kant -- Egoism in German philosophy : Johann Gottlieb Fichte -- Dialectics and history : G.W.F. Hegel -- The world as will and idea : Arthur Schopenhauer -- The father of positivism : Auguste Comte -- The saint of liberalism : John Stuart Mill -- The apostle of evolution : Herbert Spencer -- Dialectics and materialism : Karl Marx and Friedrich Engels -- Salvation without a savior : Friedrich Nietzsche -- The advent of existentialism : Soren Kierkegaard -- The return to enlightenment : Ernst Mach.
"A Mentor book."
Includes bibliographical references (pages 275-277) and index.
Keywords: Philosophy, Modern -- 19th century; Ideology -- History -- 19th century